2019
DOI: 10.1088/1612-202x/ab2be4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the Earth’s curved spacetime on Gaussian quantum coherence

Abstract: Light wave-packets propagating from the Earth to satellites will be deformed by the curved background spacetime of the Earth, thus influencing the quantum state of light. We show that Gaussian coherence of photon pairs, which are initially prepared in a two-mode squeezed state, is affected by the curved spacetime background of the Earth. We demonstrate that quantum coherence of the state increases for a specific range of height h and then gradually approaches a finite value with further increasing height of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…However, one could also perceive that the quantum discord is more sensitive to the change of frequency parameter B than the classical correlation. Finally, in the framework of a quantity describing the change rate of three types of correlations, we detect a special (16) www.nature.com/scientificreports/ height ( h = 2r A ) at which the blueshift and redshift effects are offset. More importantly, the changes of correlations generated by the total gravitational frequency shift is determined at the level of < 0.5% within the satellite's height at geostationary Earth orbits.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, one could also perceive that the quantum discord is more sensitive to the change of frequency parameter B than the classical correlation. Finally, in the framework of a quantity describing the change rate of three types of correlations, we detect a special (16) www.nature.com/scientificreports/ height ( h = 2r A ) at which the blueshift and redshift effects are offset. More importantly, the changes of correlations generated by the total gravitational frequency shift is determined at the level of < 0.5% within the satellite's height at geostationary Earth orbits.…”
Section: Discussionmentioning
confidence: 89%
“…For instance, it was found in 14 that there would be inevitable losses of quantum resources in the estimation of the Schwarzschild radius. Furthermore, a quantitative investigation of the dynamics of satellite-based quantum steering and coherence has been presented in 15,16 , given the curved background space-time of the Earth. Nowadays, it is possible to explore those quantum correlations with quantum discord acting as a resource in quantum protocols, as well as the correlations related to the practical implementation of many quantum information schemes in relativistic quantum systems, such as, quantum key distribution through satellite nodes 17 and other quantum information tasks [18][19][20][21][22][23] .…”
mentioning
confidence: 99%
“…Satellites can also be used to probe other effects associated with entanglement. For instance, it has been shown that the entanglement of Gaussian states [405,406], two mode-squeezed states [408] and multipartite W-states [409] show measurable changes in curved spacetime. Additionally, curved spacetime has been theorised to create entanglement [410].…”
Section: General Relativity and Quantum Field Theory In Curved Spacetimementioning
confidence: 99%
“…For instance, it was found in 14 that there would be inevitable losses of quantum resources in the estimation of the Schwarzschild radius. Furthermore, a quantitative investigation of the dynamics of satellite-based quantum steering and coherence has been presented in 15,16 , given the curved background space-time of the Earth. Nowadays, it is possible to explore those quantum correlations (with quantum discord acting as resources in quantum protocol) and the correlations in relativistic quantum systems (which is related to the practical implementation of many quantum information schemes, i.e., quantum key distribution through satellite nodes 17 and other quantum information tasks [18][19][20][21][22][23] ).…”
Section: Introductionmentioning
confidence: 99%